US economic outlock for 1973 - Robert G. Wertheimer (Intereconomics, 1973)
The electorate has spoken — alea jacta est — re-electing President Nixon in an old-fashioned landslide for another four years' term. What is to be expected in the internal and external economic sphere during 1973?
Keywords: 330; Trade And Development